Effect of Risk Analysis in Marketing Aspects Against with Determination Mega Bank Branch Locations - Prasastia, Nucki; Andinar Pertiwi, RR Ajeng (Journal of Economics and Business UBS, 2019)
Banks have made dramatic changes to risk management in the past decade—and the pace of change shows no signs of slowing. Risk management in banking has been transformed over the past decade, largely in response to regulations that emerged from the global financial crisis and the fines levied in its wake.  While Customer expectations are rising in line with changing technology. This study aimed to find out the relationship between risk on the marketing aspect of Mega Bank’s Branch Office Opening. The case study was taken precisely in the Palu province of Central Sulawesi. This research was conducted using qualitative methods. This analysis describes more about the Mega Bank branch office opening. After that analisis will associated with the risk in the marketing aspect when branches have been opened. In the implementation, the Mega Bank get some signs there will be a risk, so the Mega Bank management should perform analysis early before creating business feasibility study. The data used are deposits, loans, market share and internal. The data coming from Indonesia Bank, Badan Pusat Statistik, Mega Bank internal data and other supporting data.